Pelatihan Desain Pagar Rumah Futuristik Menggunakan Coreldraw Pada Kelompok Pemuda Perumahan Alam Hijau Jember - Warisaji, Taufiq Timur; Rosyidah, Ulya Anisatur; Nusanto, Baktiawan (Journal Of Humanities Community Empowerment, 2023)
Mastery of graphic design is very important because of the importance of graphic design in organizational or community activities. The training session took place at Darma Alam Housing Complex, Jember on 20 May 2023. The workshop participants consisted of youth from Darma Alam Housing as well as officials from the local Rukun Warga. Before starting to use the Corel Draw application, participants were given graphic design material to read. This dedication activity emphasizes hands-on practice, so that a lot of time is spent practicing so that innovations in graphic design can be utilized immediately. The participants' understanding of the participant's visual design was quite strong, as evidenced by the participants' ability to remember the type and position of the tools used according to their needs. This course helps young people improve their graphic design skills by utilizing the Corel Draw application. Furthermore, the purpose of this activity is to foster creativity in the world of computers, especially graphic design. Based on the findings and discussion of Corel Draw graphic design training, it can be concluded that Darma Alam Housing youth partners can develop their creativity in the field of Corel Draw graphic design. Partners have also demonstrated design skills using Corel Draw tools, as well as knowledge of tips and methods for creating graphic designs, especially fences